Dziecko w pogoni za szczęściem. Pozory szczęśliwego dzieciństwa - Kuszak, Kinga (Kultura-Społeczeństwo-Edukacja, 2018)
The article tackles the issue of the contemporary childhood. The author notes that in search of a happy childhood, the essence of childhood is often lost. Instead of a genuinely careless and happy childhood, the reality created for today’s children is full of appearances. In her discussion of the subject, the author refers to a selected approach to happiness. She also identifies, based on Janusz Czapiński’s proposal, the difference between happiness and feeling happy. She points to the fact that 21st-century life is an endless chase after the future, lacking the opportunity to focus on here and now. Childhood too is treated as a race towards adulthood. In the course of her argument, the author identifies and describes selected styles of creating a happy childhood: an abundant childhood, an active childhood, a childhood in the limelight, a boundless childhood, a childhood among people. Concluding her argument, the author proposes that instead of chasing happiness and creating the appearances of a happy childhood for children, it might be better to simply slow down the pace of life when possible and value the present. After all, “sharing the joy of life is the essence of a satisfying child-parent relationship”. The author also discusses the role of the teacher as a person supporting the parents in their parenting roles.